What Is New in Glaucoma: From Treatment to Biological Perspectives - Raffaele Nuzzi; Paola Marolo; Alessia Nuzzi (Journal of Ophthalmology)
Glaucoma is a chronic silent disease and an irreversible cause of blindness worldwide. Research has made many efforts to improve disease control and especially to anticipate both early diagnosis and treatment of advanced stages of glaucoma. In terms of prevention, networking between professionals and nonprofessionals is an important goal to disseminate information and help diagnose the disease early. On the other hand, the most recent approaches to treat glaucoma outcomes in its advanced stages include electrical stimulation, stem cells, exosomes, extracellular vesicles, and growth factors. Finally, neuronal plasticity-based rehabilitation methods are being studied to reeducate patients in order to stimulate their residual visual capacity. This review provides an overview of new approaches to future possible glaucoma treatment modalities and gives insight into the perspectives available nowadays in this field.